Teachers role of islamic religious education in strengthening the values of islamic character of students of SMP IT Ibn Mas’ud Wates Yogyakarta - Pahlevi, Muhammad Syafrizal; Sutarman, Sutarman; Ahmadi, Ahmadi (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2024)
This research aims to examine in depth: (1) the role of PAI teachers in strengthening the Islamic character values of students at Ibnu Mas'ud IT Middle School; (2) supporting and inhibiting factors in strengthening the Islamic character values of students at Ibnu Mas'ud IT Middle School. This research uses a qualitative method with a descriptive approach. Data collection techniques in this research include observation, interviews, and documentation. The results of this research show that the role of PAI teachers in strengthening the Islamic character values of students at SMP IT Ibnu Mas'ud is providing learning and material about PAI by instilling character education, holding Islamic Personal Development activities where these activities are in the form of solutions and motivation for students. The supporting and inhibiting factors for the role of PAI teachers in strengthening the Islamic character of students at Ibnu Mas'ud IT Middle School are the supporting factors: (1) students' awareness; (2) the existence of facilities and infrastructure; (3) program supervision; (4) socialize with the surrounding community. Meanwhile, the factors inhibiting the role of PAI teachers are (1) lack of individual awareness; (2) limited facilities and infrastructure; (3) indifference; (4) lack of program evaluation from the Leadership.